Structural and Magnetic Properties of Ni-doped Yttrium Iron Garnet (Y3Fe5-XNixO12) Nanopowders Synthesized by Self-Combustion Method - Puspitasari, P. (Universidade Federal de Sao Carlos, 2022)
This research aimed to investigate the structural and magnetic properties of Yttrium Iron Garnet by Ni-doped using self-combustion method. Ni-doped directly changed the structure into Y3Fe5-XNixO12 (x=0.00, 0.02, 0.04, 0.06, 0.08). Self-combustion method was obtained by stirring raw materials at room temperature (27Â°â28Â°C) and heated at 150Â°C until combustion occurred. The samples were sintered at 900Â°C with 120 minutes holding time. The phase identification revealed the cubic structure of garnet phase with the crystallite size from 62.73â62.87 nm. The molecular bonding from molecular bonding displayed Ni-O and Fe-O bonds, while the magnetic properties shown the highest saturation magnetization of 27.04 emu/g in the sample with additional Ni x=0.02, the highest magnetic remenance of 16.09 in the sample Ni x=0.02, and the highest coercivity of 0.029 in the sample with Ni x=0.08. This research, by adding nickel element, shows that the coercivity of Y3Fe5-XNixO12 decreased when the particle size is increased. The increase in Ni concentration as doping material cause the double exchange interaction and affected the lattice parameter, molecular bond, and magnetic properties. Â© 2022 Universidade Federal de Sao Carlos. All rights reserved.